APLIKASI PENDAFTARAN PASIEN RAWAT JALAN RUMAH SAKIT MEILIA CIBUBUR BERBASIS WEB - Edo Nado Candra; Juarni Siregar; Sinta Rukiastiandari (Universitas Sahid Surakarta, 2019)
The purpose of this research is to build Application of Outpatient Registration in the hope that patient registration process easier to do, efficient and has been usingthe latest technology by using Web-based application. In the event of a problem can be detected and repaired more easily and quickly. The current system at Meilia CibuburHospital is a hospital-based hospital system, a running system that has been running well and has helped get the required data officer. But on the desktop technology-based application side is limited by the access that must be in one network of Meilia Hospital only. The author studied the existing system and make the application of Outpatient Registration with the aim of renewal of hospital application technology into web-based application of course with no disrupt and almost the same for the workflow officers with existing systems.